Health and quality of life among older rural people in Purworejo District, Indonesia - Nawi Ng; Mohammad Hakimi; Peter Byass; Siswanto Wilopo; Stig Wall (Taylor & Francis Group, 2010)
Introduction: Increasing life expectancy and longevity for people in many highly populated low- and middle-income countries has led to an increase in the number of older people. The population aged 60 years and over in Indonesia is projected to increase from 8.4% in 2005 to 25% in 2050. Understanding the determinants of healthy ageing is essential in targeting health-promotion programmes for older people in Indonesia. Objective: To describe patterns of socio-economic and demographic factors associated with health status, and to identify any spatial clustering of poor health among older people in Indonesia. Methods: In 2007, the WHO Study on global AGEing and adult health (SAGE) was conducted among 14,958 people aged 50 years and over in Purworejo District, Central Java, Indonesia. Three outcome measures were used in this analysis: self-reported quality of life (QoL), self-reported functioning and disability, and overall health score calculated from self-reported health over eight health domains. The factors associated with each health outcome were identified using multivariable logistic regression. Purely spatial analysis using Poisson regression was conducted to identify clusters of households with poor health outcomes. Results: Women, older age groups, people not in any marital relationship and low educational and socio-economic levels were associated with poor health outcomes, regardless of the health indices used. Older people with low educational and socio-economic status (SES) had 3.4 times higher odds of being in the worst QoL quintile (OR=3.35; 95% CI=2.73–4.11) as compared to people with high education and high SES. This disadvantaged group also had higher odds of being in the worst functioning and most disabled quintile (OR=1.67; 95% CI=1.35–2.06) and the lowest overall health score quintile (OR=1.66; 95% CI=1.36–2.03). Poor health and QoL are not randomly distributed among the population over 50 years old in Purworejo District, Indonesia. Spatial analysis showed that clusters of households with at least one member being in the worst quintiles of QoL, functioning and health score intersected in the central part of Purworejo District, which is a semi-urban area with more developed economic activities compared with other areas in the district. Conclusion: Being female, old, unmarried and having low educational and socio-economic levels were significantly associated with poor self-reported QoL, health status and disability among older people in Purworejo District. This study showed the existence of geographical pockets of vulnerable older people in Purworejo District, and emphasized the need to take immediate action to address issues of older people's health and QoL.